2019
DOI: 10.20474/jabs-5.5.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of employee happiness on performance of employees in public organization in United Arab Emirates

Abstract: The study operationalized employee happiness into performance appraisal, lexible working hours, promotion, rewards, and recognition, income, peer and supervisor support, workload, and workplace environment. The data was collected from 319 employees working in Abu Dhabi and Dubai using a questionnaire "The effect of employee spirituality and emotional wellness toward the relationship between employee happiness and employee performance 2019". The indings were derived using Smart Partial Least Squares (PLS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Empirical evidences from other sources indicate that job satisfaction positively effects psychological well-being [23,24] , organisational commitment [25] , citizenship behaviour [26] , and performance [27] . In the context of public sector in United Arab Emirates (UAE), Awada et al [28] concluded that income, workplace environment, promotion, reward, recognition and supervisor and peer support all positively influence employee performance. Also training provided to the employees in private insurance sector in Coimbatore, India was found to improve employee performance and enhance productivity [29] .…”
Section: Relationships: Gnh In Corporation Psychological Capital and ...mentioning
confidence: 99%
“…Empirical evidences from other sources indicate that job satisfaction positively effects psychological well-being [23,24] , organisational commitment [25] , citizenship behaviour [26] , and performance [27] . In the context of public sector in United Arab Emirates (UAE), Awada et al [28] concluded that income, workplace environment, promotion, reward, recognition and supervisor and peer support all positively influence employee performance. Also training provided to the employees in private insurance sector in Coimbatore, India was found to improve employee performance and enhance productivity [29] .…”
Section: Relationships: Gnh In Corporation Psychological Capital and ...mentioning
confidence: 99%
“…While achieving employee happiness becomes a challenge for developing countries that need to be considered especially in the UAE (Fitria, 2018). In addition, the topic of job performance has been widely debated in the literature but its association with servant leadership and employee happiness was not reported (Awada, 2019). However, different approaches to studying employee job performance circulate in today's literature should be discussed based on the perspective of happiness and leadership disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Company allows employees a level of freedom to create their flexible work schedules Abid and Barech, (2017) and Awada et al (2019) Employees are encouraged to learn from their mistakes rather than fear them to bring creative solutions Harteis et al (2008) Employees find joy to fulfil company goals as company prioritizes good work-life balance Bataineh (2019) Company help build teams that foster a strong working relationship Fapohunda (2013) and Harvey et al (1998) Organization provides a comprehensive employee benefits programme that keep them productive and loyal Sinclair et al (2005) (Table A1 Continued)…”
Section: Work On Feedbackmentioning
confidence: 99%